2021
DOI: 10.15252/embj.2021108708
|View full text |Cite
|
Sign up to set email alerts
|

Distinct heterochromatin‐like domains promote transcriptional memory and silence parasitic genetic elements in bacteria

Abstract: There is increasing evidence that prokaryotes maintain chromosome structure, which in turn impacts gene expression. We recently characterized densely occupied, multi-kilobase regions in the E. coli genome that are transcriptionally silent, similar to eukaryotic heterochromatin. These extended protein occupancy domains (EPODs) span genomic regions containing genes encoding metabolic pathways as well as parasitic elements such as prophages. Here, we investigate the contributions of nucleoidassociated proteins (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(48 citation statements)
references
References 96 publications
17
31
0
Order By: Relevance
“…Several molecular dynamics studies confirmed that micromolar-range increases in NAP levels enhance nucleoid compaction by inducing various protein-DNA structures from bridges to bundles and filaments (Figure 1) as expected (Brackley et al, 2013;Koşar et al, 2022). Consistently, a very recent experimental study has demonstrated the regulatory effects of such multiprotein-DNA complexes in living E. coli (Amemiya et al, 2022). Notably, the different protein-DNA complexes and resulting structures could have different regularity strengths, as demonstrated for H-NS TFs, for which bridged-filamentous structures are more efficient in transcription repression than isolated filaments (Singh et al, 2014;Kotlajich et al, 2015).…”
Section: Introductionsupporting
confidence: 77%
See 2 more Smart Citations
“…Several molecular dynamics studies confirmed that micromolar-range increases in NAP levels enhance nucleoid compaction by inducing various protein-DNA structures from bridges to bundles and filaments (Figure 1) as expected (Brackley et al, 2013;Koşar et al, 2022). Consistently, a very recent experimental study has demonstrated the regulatory effects of such multiprotein-DNA complexes in living E. coli (Amemiya et al, 2022). Notably, the different protein-DNA complexes and resulting structures could have different regularity strengths, as demonstrated for H-NS TFs, for which bridged-filamentous structures are more efficient in transcription repression than isolated filaments (Singh et al, 2014;Kotlajich et al, 2015).…”
Section: Introductionsupporting
confidence: 77%
“…We also argue that, in the case of dual-purpose bacterial TFs that have both transcriptional and structural roles, TF levels can modulate the exposure of a gene to transcription-related proteins by changing the chromosomal structure in a concentration-dependent manner and thus function as a regulatory component. Consistently, during the preparation of this article, an experimental study demonstrated the possibility of such regulation in E. coli (Amemiya et al, 2022). For repressive roles of a TF, higher protein levels can coat generich regions via binding to DNA nonspecifically.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…nucleoid-associated proteins (22). We have recently shown that Hfq and Fis are required for silencing prophages across the genome and make up the main protein components of EPODs across many of these regions (23). Moreover, we found that loss of fis and hfq is synthetic lethal in a prophage-dependent manner (23).…”
Section: Polyp and Hfq Cooperate In Silencing Of Mgesmentioning
confidence: 90%
“…Intriguingly, the CTR can form an amyloidlike structure [25] that can bind to DNA, making the DNA molecule more compact and condensed [26][27][28]. Moreover, Hfq and its CTR can interact with and stabilize G-quadruplex structures [29,30], influence the mechanical properties of the DNA [31], modulate genomic instability [29,30,32] and drive bacterial heterochromatin formation [28,33].…”
Section: Introductionmentioning
confidence: 99%